2021
DOI: 10.1002/jgc4.1402
|View full text |Cite
|
Sign up to set email alerts
|

How are uncertain prenatal genetic results perceived and managed two years after they were received? A qualitative interview study

Abstract: Chromosomal microarray has considerably improved our ability to identify or dismiss genetic conditions in the unborn child. However, this detailed analysis also reveals copy number variants (CNVs) of unknown or uncertain significance, in which the specific child's prognosis can be difficult to predict. Little is known about the longer‐term impacts of receiving an uncertain prenatal CNV result. Our qualitative study explored how such a result was perceived and managed in everyday life, 2 years after it was rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…An example is 15q11 deletion and duplication 19 . The reporting and the counseling of susceptibility loci is described elsewhere 20‐22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is 15q11 deletion and duplication 19 . The reporting and the counseling of susceptibility loci is described elsewhere 20‐22 …”
Section: Discussionmentioning
confidence: 99%
“…19 The reporting and the counseling of susceptibility loci is described elsewhere. [20][21][22] Thus, we advocate provision of a better service after the transition from prenatal karyotyping to CMA. As we gained experience during the transition, we realized that we need people with diverse and overlapping skills, such as fetal medicine specialists, genetic specialists, laboratory geneticists and biotechnicians, to provide the best data interpretation and counseling, and we have also clearly benefitted from the help of anthropologists and the hospital chaplain.…”
Section: Discussionmentioning
confidence: 99%
“…Only a minority of our respondents were indifferent to their results. Previous studies showed that indeed women range in their anxiety/stress levels, ranging from short‐term anxiety (only during the pregnancy) to long‐term worry, even a few years after the child is born 14,27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that indeed women range in their anxiety/stress levels, ranging from short-term anxiety (only during the pregnancy) to longterm worry, even a few years after the child is born. 14,27,28 Although interviewees in our study received the CMA results from a genetic counselor/medical geneticist, they all sought further advice and information before making a decision regarding the continuation or termination of their pregnancy. A growing literature shows that patients/families with rare diseases often seek information and support through social media during the diagnostic odyssey, and after a diagnosis is reached.…”
Section: Discussionmentioning
confidence: 99%